Exploring Anisotropy Contributions in Mn x Co1-x Fe2O4 Ferrite Nanoparticles for Biomedical Applications - Gerina, Marianna; Sanna Angotzi, Marco; Mameli, Valentina; Mazur, Michal; Rusta, Nicoletta; Balica, Elena; Hrubovcak, Pavol; Cannas, Carla; Honecker, Dirk; Zákutná, Dominika (ACS applied nano materials, 2024)
Designing well-defined magnetic nanomaterials is crucial for various applications, and it demands a comprehensive understanding of their magnetic properties at the microscopic level. In this study, we investigate the contributions to the total anisotropy of Mn/Co mixed spinel nanoparticles. By employing neutron measurements sensitive to the spatially resolved surface anisotropy with sub-Å space resolution, we reveal an additional contribution to the anisotropy constant arising from shape anisotropy and interparticle interactions. Our findings shed light on the intricate interplay among chemical composition, microstructure, morphology, and surface effects, providing valuable insights for the design of advanced magnetic nanomaterials for AC biomedical applications, such as cancer treatment by magnetic fluid hyperthermia.